1999
DOI: 10.22358/jafs/69129/1999
|View full text |Cite
|
Sign up to set email alerts
|

Performance, body and carcass composition and bone characteristics of pigs fed rapeseed and soyabean meal-cereal diets supplemented with microbial phytase

Abstract: Thirty-three female pigs from 25 to 70 kg body weight were fed isocaloric and isoprotein diets composed of rapeseed (RSM) or soyabean meal (SBM) and a wheat-barley mixture with high intrinsic phytase content (over 900 FTU/kg). Basal diets containing 0.19-0.20% of digestible P were unsupplemented or supplemented with either microbial phytase (1000 FTU/kg, Natuphos®) or dicalcium phosphate to the level of 0.25% recommended for growing pigs. Apparent digestibility of nutrients, growth performance, carcass value, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 14 publications
2
7
0
Order By: Relevance
“…These inconsistencies can be associated with variations in 1) the origin and concentration of the PP, 2) the origin of the phytase, 3) the real phytase activity, and 4) the dietary Ca and P concentrations of the reference diet (Selle and Ravindran, 2008). The model did indeed show an effect of the first 3 listed sources of variation, A positive relationship between substrate concentration and the magnitude of the response to dietary phytase supplementation was depicted by the model, in agreement with the findings of Fandrejewski et al, (1999) and Sands et al (2009). This observation and the model results corroborate the statement by Selle and Ravindran (2008) that the interaction between phytate and phytase has to be considered when giving dietary recommendations and optimizing the efficiency with which phytase releases P from phytate.…”
Section: Prediction Of the Effect Of Phytase On P And Ca Utilizationsupporting
confidence: 82%
“…These inconsistencies can be associated with variations in 1) the origin and concentration of the PP, 2) the origin of the phytase, 3) the real phytase activity, and 4) the dietary Ca and P concentrations of the reference diet (Selle and Ravindran, 2008). The model did indeed show an effect of the first 3 listed sources of variation, A positive relationship between substrate concentration and the magnitude of the response to dietary phytase supplementation was depicted by the model, in agreement with the findings of Fandrejewski et al, (1999) and Sands et al (2009). This observation and the model results corroborate the statement by Selle and Ravindran (2008) that the interaction between phytate and phytase has to be considered when giving dietary recommendations and optimizing the efficiency with which phytase releases P from phytate.…”
Section: Prediction Of the Effect Of Phytase On P And Ca Utilizationsupporting
confidence: 82%
“…Phytase elicited improvements in P digestibility when assessed over the total tract was 51.2% in the high-phytin and 39.2% in the low-phytin diet. Fandrejewski et al (1999) reported similar results when diets containing rapeseed meal as the protein source compared with diets containing soybean meal as the protein source were fed to pigs. This finding indicates that the response to exogenous microbial phytase is greater when added to a diet containing a greater concentration of phytin.…”
Section: Growth and Ileal Aa Digestibility Response To Phytase And Phmentioning
confidence: 73%
“…Ketaren et al [27] found an increase in protein accretion in female pigs supplemented with phytase (1,000 FYT/kg feed) during 35 days of the growing period, suggesting that the enzyme contributes to increasing the utilization of protein from soybean meal. Other authors, however, reported that the inclusion of 500 or 1,000 FYT/kg feed did not result in significant differences in performance or protein deposition in both females and castrated males during the growing phase [33,34].…”
Section: Discussionmentioning
confidence: 99%